2008
DOI: 10.4067/s0717-65382008000100013
|View full text |Cite
|
Sign up to set email alerts
|

Dieta De Lycalopex Griseus (Gray, 1837) (Mammalia: Canidae) en La Depresion Intermedia Del Sur De Chile

Abstract: A study about food habits of chilla (Lycalopex griseus) was done in a sector of the intermediate depression of southern Chile, called Predio Rucamanque, Region de la Araucanía. Faeces were collected through three seasons of the year, identifying their diet composition. Results show a trend towards small mammals followed by birds, and in a lesser ratio, insects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
3
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 2 publications
3
22
3
2
Order By: Relevance
“…), increasing the vulnerability of those prey that share the same microhabitat. It should be noted that the Colocolo opossum is the prey of native terrestrial carnivores such as the gray fox (Lycalopex griseus (Gray, 1837); Martínez et al, 1993;Rau et al, 1995;Zúñiga et al, 2008) 2007). They probably capture these marsupials scratching and exploring the fallen logs on the edge or inside the forest.…”
Section: Resultsmentioning
confidence: 99%
“…), increasing the vulnerability of those prey that share the same microhabitat. It should be noted that the Colocolo opossum is the prey of native terrestrial carnivores such as the gray fox (Lycalopex griseus (Gray, 1837); Martínez et al, 1993;Rau et al, 1995;Zúñiga et al, 2008) 2007). They probably capture these marsupials scratching and exploring the fallen logs on the edge or inside the forest.…”
Section: Resultsmentioning
confidence: 99%
“…It has an area of 435 ha, an average altitude of 376 m, being 62% of its area between 201 and 400 masl. The climate is temperate and humid, with an average annual temperature and rainfall of 1,400 mm and 12ºC, respectively (Zúñiga et al, 2008 (San Martín et al, 2008).…”
Section: Site Characteristicsmentioning
confidence: 99%
“…For birds, we used a mean weight (37.0 g, N = 90) for: (i) species with previous foraging records [e.g. Turdus falcklandii Quoy & Gaimard, 1824, Xolmis pyrope (Kittlitz, 1830) Zúñiga et al 2008]; and (ii) passerine birds frequent in the study area (CEA 2001). Weights were obtained from the Francisco Behn Bird Collection deposited in the Senckenberg Museum, Frankfurt, Germany (Norambuena & Riquelme 2014).…”
Section: Trophic Analysismentioning
confidence: 99%
“…Research into L. griseus diet has shown that the most important prey by biomass are mammals, followed by birds and invertebrates; it has been shown for the latter item that diversity and frequency vary with latitude (Yáñez & Jaksic 1978;Jaksic et al 1980Jaksic et al , 1983Jiménez 1993;Marquet et al 1993;Martínez et al 1993;Johnson & Franklin 1994;Rau et al 1995;Correa & Roa 2005;Zúñiga et al 2008). However, description of the prey available in the habitats studied is deficient, which prevents further studies on its dietary selectivity (ex-cept Martínez et al 1993;Rau et al 1995), its predatory response and its role in determining the abundance of prey (Jaksic 1989).…”
Section: Introductionmentioning
confidence: 99%